The Current State of Decision Support Systems in Education on the Basis of Factual Data (Review and Problem Statement) - N. I. Listopad; A. V. Zhukovskaja (Цифровая трансформация)
The article deals with the problem of creating a decision support system in the field of education –  an unified intelligent platform for the collection, processing, analysis and presentation of factual data on the basis of client-server applications as well as using the "cloud" technologies, which will integrate and optimize disjointed base and data banks for different levels of education to solve a range of problems, including planning, monitoring and forecasting the branch development  in the short and long term.